2018
DOI: 10.1089/ars.2017.7178
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 and SIRT6 Signaling Pathways in Cardiovascular Disease Protection

Abstract: Significance: Oxidative stress represents the common hallmark of pathological conditions associated with cardiovascular disease (CVD), including atherosclerosis, heart failure, hypertension, aging, diabetes, and other vascular system-related diseases. The sirtuin (SIRT) family, comprising seven proteins (SIRT1-SIRT7) sharing a highly conserved nicotinamide adenine dinucleotide (NAD + )-binding catalytic domain, attracted a great attention for the past few years as stress adaptor and epigenetic enzymes involved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
246
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 295 publications
(253 citation statements)
references
References 220 publications
(281 reference statements)
3
246
0
4
Order By: Relevance
“…Sirtuins have been implicated in glucose and lipid metabolism with an important role in various cellular metabolic pathways [40,41]. Recent studies have suggested a molecular interplay between HO-1 and sirtuin1 (SIRT1), demonstrating that upregulated expression of HO-1 activity can rescue SIRT1 expression, where the two form a "cytoprotective module" in a model of obesity [35].…”
Section: Mechanistic Insights Into Ho-1 and Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirtuins have been implicated in glucose and lipid metabolism with an important role in various cellular metabolic pathways [40,41]. Recent studies have suggested a molecular interplay between HO-1 and sirtuin1 (SIRT1), demonstrating that upregulated expression of HO-1 activity can rescue SIRT1 expression, where the two form a "cytoprotective module" in a model of obesity [35].…”
Section: Mechanistic Insights Into Ho-1 and Oxidative Stressmentioning
confidence: 99%
“…The modulatory mediators of RAS, such as angiotensin II (AngII), increases cellular heme levels by peroxynitrite inactivation, produces excessive ROS and increases the release of inflammatory cytokines while decreasing expression of HO-1 and suppressing SIRT1. This redox imbalance leads to dyslipidemia and insulin resistance [40,41,52,53]. Heme increases lipid accumulation, promotes cell enlargement, induces over-expression of adipogenic genes, such as PPARG, C/EBP-α and adipocyte protein 2 (aP2), and downregulates adiponectin [32,34,54].…”
Section: The Na/k-atpase Oxidant Amplification Loop and Ho-1: Implicamentioning
confidence: 99%
“…Alzheimer's disease 27,37 Huntington's disease, amyotrophic lateral sclerosis and spinal, bulbar muscular atrophy 37 Parkinson's disease 27 Cardiovascular diseases 20 Type-2 diabetes 20,27 that Sirt1 expressions can be a probable diagnostic tool for the detection of COPD. 59 The premature aging of the lungs results in lung inflammation, which causes cellular senescence.…”
Section: Sirt1mentioning
confidence: 99%
“…Sirtuins, initially discovered in the late1980s, are universally known as a NAD‐dependent histone deacetylases that play a complex role in the process of aging. Sirtuins are also classified as antiaging molecules; emerging sources of evidence have shown that these highly conserved enzymes play a pivotal role in pulmonary fibrosis . Sirtuins are also known as modulators involved in DNA repair, energy metabolism, apoptosis, and oxidative stress responses .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation